Profile of an occupation – geomatician - Schambeck, Arne [Verfasser] (My University, 2022)
"Natural disasters are occurring ever more frequently. The floods which hit the Eifel region in the summer of 2021 made it clear just how devastating the consequences of such events may be. The interpretation and visualisation of geodata assists in arriving at a better estimation of which areas may be struck by flooding and of how badly they could be affected. Geomaticians prepare such data and draw up risk maps. They thus make an important contribution to the interpretation of complex spatial circumstances." (BIBB-Doku)
Keywords: S 6.3.2 Techniker, Technische Sonderkräfte, Zeichner, Industriemeister (ausgenommen IT-Berufe); 370; Geomatiker; Berufsprofil; Berufsbildungsstatistik